LIVING HADIS: FENOMENA SARAPAN BERSAMA PASCA PENGAJIAN AHAD PAGI MASYARAKAT BANGAH SIDOARJO - irfan yuhadi; Nurul Budi Murtini (Al-Majaalis : Jurnal Dirasat Islamiyah, 2019)
The word “sarapan” (breakfast) comes from the word “sarap” which is added a suffix “an.” The word “sarap” is a verb which means eating something in the morning. Breakfast is food that is eaten in the morning before doing activities and it is eaten approximately one third of the food in a day. Breakfast gives a lot of benefits for the health of our body. It will be more enjoyable if it is done together. Bangah is a village located in the Gedangan district in Sidoarjo, East Java. The formulations of the problem in this research are about: (1) the concept of procuring breakfast together after Sunday morning recitation, (2) the benefits of having brakfast togehter after Sunday morning recitation, (3) the hadiths that recommend to feed others and eat together. The research in this study uses qualitative research with the study of living hadith as its research model.The results of this study indicate that: (1) the concept of procuring breakfast together after Sunday morning recitation starts from the desire to apply knowledge about the virtues and a great reward for those who feed the prosecutors of knowledge.The source for funding the activities are from the donations of the worshipers and the donors of the mosque, (2) the activity of having breakfast together after Sunday morning recitation brings a lot of positive benefits personally and socially, (3) there are hadits that recommend to feed other people and eat together.